2017
DOI: 10.1007/s00467-017-3583-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rituximab in comparison with common induction therapies in pediatric active lupus nephritis

Abstract: Efficacy and medium-term safety of RTX induction followed by MMF maintenance therapy in inducing and maintaining remission among children with LN were evident in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 33 publications
4
35
0
1
Order By: Relevance
“…Three patients died during the follow-up period (due to invasive histoplasmosis, complications of surgery, and disease progression). In the controlled trials,13,33,35,36 the relative risks of the following adverse events were not significantly different between RTX and other immunosuppressive agents (CYC/MMF): infection, 0.81 (95% CI: 0.46–1.43, P >0.05) and infusion reaction, 2.18 (95% CI: 0.43–10.98, P >0.05).…”
Section: Resultsmentioning
confidence: 90%
“…Three patients died during the follow-up period (due to invasive histoplasmosis, complications of surgery, and disease progression). In the controlled trials,13,33,35,36 the relative risks of the following adverse events were not significantly different between RTX and other immunosuppressive agents (CYC/MMF): infection, 0.81 (95% CI: 0.46–1.43, P >0.05) and infusion reaction, 2.18 (95% CI: 0.43–10.98, P >0.05).…”
Section: Resultsmentioning
confidence: 90%
“…With recent advances in understanding of the underlying pathology, utilizing targeted biological agents in SLE patients properly has resulted in a significant improvement in prognosis. Nonetheless, the search for new therapeutic strategies is relentless because of the occurrence of refractory disease [2]. Mesenchymal stem cells (MSCs) are identified as promising and alternative cells because of their self-renewal, pluripotent differentiation ability and low immunogenicity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well tolerated and has a protective effect in reducing damage accrual in the long term and confers a survival benefit in SLE patients. A Danish registry-based cohort reported an found that rituximab may improve several symptoms and signs of SLE [19,[50][51][52]. In the present study, rituximab was utilized by almost 21% of SLE population.…”
Section: Discussionmentioning
confidence: 54%
“…Clinical trials have found a promising part for rituximab in the treatment of SLE [4,50,53]. A combination of rituximab with a short-term intensive steroid treatment and low doses of intravenous cyclophosphamide may be of use as an effective therapeutic strategy to reduce the adverse events related to long-term immunosuppression [7,19,50,51,54]. However, controlled trials especially for long-term outcome studies are awaited to further define its clinical application and to improve the care of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation